2002
DOI: 10.1034/j.1600-9657.2002.00122.x
|View full text |Cite
|
Sign up to set email alerts
|

Sports dentistry and dental traumatology

Abstract: – Sports dentistry had its origins in the 1980s. More recently, the Academy for Sports Dentistry joined forces with the International Association of Dental Traumatology in cosponsoring the World Congress on Sports Dentistry and Dental Traumatology. It is the intent of the present paper to introduce readers to the arena of sports dentistry, suggest future areas for collaborative research, and stimulate authors to submit high quality, scientifically based manuscripts on sports dentistry to Dental Traumatology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
76
0
10

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(87 citation statements)
references
References 55 publications
1
76
0
10
Order By: Relevance
“…Difficulty breathing and alterations in strength and performance are related concerns about mouthguard use (22,23). However, a randomized, controlled, clinical trial found that custommade mouthguards had no such detrimental effects (23).…”
Section: Discussionmentioning
confidence: 99%
“…Difficulty breathing and alterations in strength and performance are related concerns about mouthguard use (22,23). However, a randomized, controlled, clinical trial found that custommade mouthguards had no such detrimental effects (23).…”
Section: Discussionmentioning
confidence: 99%
“…Nos Estados Unidos, apenas cinco esportes exigem o uso de protetores bucais: boxe, futebol americano, hóquei no gelo, lacrosse masculino e hóquei de campo feminino 25 , sendo que em 29 esportes/atividades físicas o uso de protetor bucal é recomendado pela American Dental Association 26 . No Brasil, entretanto, seu uso é obrigatório apenas no boxe 26 .…”
Section: Objectiveunclassified
“…Protective equipment, such as a properly fitted mouthguard, both absorbs and distributes the traumatic forces of impact, thereby reducing (but not eliminating) the incidence of dental injuries. 12,22,89,90 However, when injuries to the tooth-jaw complex do occur, they often require immediate intervention by the AT, as well as referral to the appropriate oral health care specialist. With respect to the adult permanent dentition, as for every situation, the AT's acute treatment goal is to deliver the best possible health care to the athlete.…”
Section: Background and Literature Review Planning Considerationsmentioning
confidence: 99%